Joint Centre for the Study of Regional Development Jawaharlal Nehru University - Planning Commission (Planning Commission, 1974)
Self-sufficiency in agricultural production in general and in food production in particular is one of the important objectives of agricultural planning in India. The achievement of self-sufficiency implies that the level of domestic production is at least adequate to meet the basic food needs of the existing population and provide all the raw materials required by the industry. Moreover, over the years the agricultural output must grow to meet both the increasing demands of food because of increases in population and projected increases in income as well as At he growth in demand for agricultural raw materials from industry. Population, in India, grew at an annual compound rate of 2.24 per cent per. annum during 1961 to 1971.
Perspective Planning Division (Planning Commission)
Socio Economic Research Planning Commission